Water supplementation of Moringa oleifera as a substitute for antibiotics on performance and blood parameters of broiler chickens (Journal of the Bangladesh Agricultural University, 2018)
There is a serious public health concern of the use of antibiotics sub-therapeutically and/or as growth promoter in poultry feed and water. Therefore, there is an urgent need for alternatives. Moringa oleifera is a phytobiotic, which has been reported to possess antimicrobial and immuno-modulatory properties. This study aimed to investigate the effects of aqueous M. oleifera leaf extract (MOLE) supplementation on growth performance and hematological indices of broiler chickens. The 36 day-old broiler chicks (Cobb 500) were randomly divided into three dietary groups (group A, B and C) having 12 birds in each. The group A was considered as negative control which had received the basal diet and fresh drinking water. The group B was fed with basal diet and antibiotics (Ciprofloxacin) plus Vitamin B-complex mixed drinking water(Positive control). The group C was fed with basal diet and drinking water supplemented with 1% MOLE. Body weight, feed intake and feed conversion ratios of the birds were recorded on weekly basis. On day 35th of the feeding trail, blood samples from five birds per replicate were used for the study of hematological indices. Birds under Group C attained intermediate body weight (1892 g) and best FCR (1.48) those were comparable with that of Group B but better (p0.05) internal organs weight in Group C compared to other groups. However, zero mortality rate and similar hematological indices were observed in the birds across the treatments. Here, the results suggested that, the aqueous MOLE can be included in the drinking water of broiler chicken for reduced feed intake and improved feed conversion efficiency and it can be considered as an alternate to synthetic antibiotics as growth promoter to fight the emergence of antibiotic resistance phenomena in poultry industry.J. Bangladesh Agril. Univ. 16(2): 266-270, August 2018